Ethnopedagogy of Early-Age Santri: Javanese Value-Based Parenting in Constructing Student Obedience (Journal Of Islamic Education And Pesantren, 2025)
This study aims to investigate the role of Pesantren (Islamic boarding school) parenting based on Javanese values in constructing compliance among residential students (siswa mukim) at MI Al-Ghozaliyah Jogoroto Jombang, as well as to identify the supporting and inhibiting factors. The parenting style applied in this environment is grounded in noble Javanese cultural values such as sungkan (reluctant respect), tata krama (etiquette), rukun (harmony), nrimo (acceptance), and manut (obedience), which are believed to shape student compliance with both Madrasah and Pesantren regulations. This research employs a qualitative approach with a case study design. Data collection was conducted through observation, documentation, and in-depth interviews with the Head of Madrasah, class teachers, boarding supervisors, and residential students. Data analysis followed the stages of data reduction, data display, conclusion drawing, and verification. Data validity was established through source and technique triangulation. The results indicate that Pesantren parenting based on Javanese values plays a significant role in instilling compliance through various strategies, including the habituation of polite and orderly behavior, a collaborative approach between the school and the boarding house, role modeling, and the provision of emotional and spiritual support. Furthermore, consistent religious values and a disciplined environment reinforce the students' compliant character. The study concludes that Pesantren parenting grounded in Javanese values is effective in fostering compliance among MI students, particularly residential ones, through the internalization of local cultural values harmonized with Islamic values and role modeling in daily life.